2020
DOI: 10.1111/jwas.12733
|View full text |Cite
|
Sign up to set email alerts
|

Effect of understocking density of channel catfish fingerlings in intensively aerated multiple‐batch production

Abstract: Multiple‐batch production is the most widely practiced method of raising channel catfish. Producers are increasingly adopting intensified production practices in multiple‐batch systems by increasing stocking density and aeration rates as a means to improve cost efficiencies. Proven stocking recommendations are required for the efficient implementation of recent developments in multiple‐batch production. Twelve 0.4‐ha ponds were understocked with 17,484, 20,612, and 26,124 fingerlings/ha (mean weight = 40 g/fis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 40 publications
(71 reference statements)
0
11
0
Order By: Relevance
“…Although all three examined production systems were deemed profitable, the MB system, having the second-highest gross revenue, had the highest percentage of oversized fish (12%) compared to the SB (4%) and SP (4%) systems. This may be due to the continuous production schedule followed in the MB system, involving multiple stockings and partial harvests, which allow a certain number of larger and/or submarketable fish to stay in the ponds for the next cycle (Hanson et al 2020;Kumar et al 2021). The current study also showed that the average dockage loss can be $0.12/kg for undersized fish and $0.38/kg for oversized fish from the three production systems.…”
Section: Discussionmentioning
confidence: 68%
See 4 more Smart Citations
“…Although all three examined production systems were deemed profitable, the MB system, having the second-highest gross revenue, had the highest percentage of oversized fish (12%) compared to the SB (4%) and SP (4%) systems. This may be due to the continuous production schedule followed in the MB system, involving multiple stockings and partial harvests, which allow a certain number of larger and/or submarketable fish to stay in the ponds for the next cycle (Hanson et al 2020;Kumar et al 2021). The current study also showed that the average dockage loss can be $0.12/kg for undersized fish and $0.38/kg for oversized fish from the three production systems.…”
Section: Discussionmentioning
confidence: 68%
“…Production advantages of hybrid catfish include better growth, crowding tolerance, lower feed conversion ratio (FCR; a measure of the efficiency of converting fish feed into fish biomass), and greater disease resistance (Dunham and Masser 2012;Li and Robinson 2012). These characteristics allow hybrid catfish to be used in a more intensive production system and achieve economies of scale by spreading the total fixed costs over greater fish production (Kumar et al 2018(Kumar et al , 2021).…”
mentioning
confidence: 99%
See 3 more Smart Citations